ChemInform Abstract: Acentric Pseudo‐Kagome Structures: The Solid Solution (Co1‐xNix) 3Sb4O6F6. Issue 33 (19th August 2014) - Hu, Shichao; Johnsson, Mats; Lemmens, Peter; Schmid, Daniel; Menzel, Dirk; Tapp, Joshua; Moeller, Angela
Abstract (Co1‐xNix) 3Sb4O6F6 (x = 0, 0.25, 0.5, 0.75, 1) is prepared by hydrothermal treatment of CoF2 and/or NiF2, and Sb2O3 (autoclave, 230 °C, 4 d).